A new species of Odontophrynus (Anura, Odontophrynidae) from the southern portion of the Mantiqueira mountains - Moroti, Matheus de Toledo; Pedrozo, Mariana; Severgnini, Marcos Rafael; Augusto-Alves, Guilherme; Dena, Simone; Martins, Itamar Alves; Nunes, Ivan; Muscat, Edelcio (European Journal of Taxonomy, 2022)
Using an integrative approach (morphology of the adult and larvae, bioacoustics, osteology, karyotype, and molecular data), we described a new tetraploid species of Odontophrynus to the Mantiqueira mountain range, in southeastern Brazil. The data suggest that Odontophrynus toledoi sp. nov., O. juquinha and Odontophrynus sp. (aff. juquinha) comprise a clade with specimens distributed along three distinct mountain ranges in Brazil: Mantiqueira (O. toledoi sp. nov.) and Espinhaço (O. juquinha) mountains, both in southeastern Brazil, and Diamantina Plateau (O. aff. juquinha), in northeastern Brazil. The new species is morphologically similar and closely related to O. juquinha, but is distinguished in morphology (both adult and larval), karyotype (O. toledoi sp. nov. is tetraploid and O. juquinha is diploid), and corroborated by phylogenetic inferences. We also show that these species do not exchange haplotypes in the 16s gene. Furthermore, although the raw acoustic parameters of Odontophrynus toledoi sp. nov. and O. juquinha overlap at the limits of their ranges, we found a clear difference in the acoustic space structure.